Case Report of a Hidden Intruder—Extremely Rare Presentation of Hydatidosis as a Nuchal Tumoural Mass - Voicu, Dragoș F.; Popazu, Constantin; Râșnoveanu, Delia Mihaela; Mihalache, Daniela; Toma, Alexandra (British Journal of Biomedical Science, 2024)
Introduction: The parasitic tapeworm impersonated by the larvae of Echinococcus granulosus represents the aetiology of the hydatid pathology. The predilect site of invasion is the liver, but there are other cases of different localization all over the body, regardless of the type of invaded tissue. Soft tissue hydatidosis can be a real challenge for the clinician in terms of the diagnosis, and it might generate various complications such as anaphylactic shock. The aim of the present work is to illustrate a unique case of primary hydatidosis located in the nuchal region. Case Report: We report the case of a 68-year-old male patient, a zootechnic, who presented at the hospital with a tumoural mass (dimension: about 12/10 cm) located in the nuchal region. The complex approach needed consisted of surgical therapy along with histopathological confirmation of the diagnostic and antiparasitic medication, which led to a complete recovery with a low probability of recurrence. Discussion: Encounters with patients with primary soft tissue hydatidosis are exceptionally rare, but the surgeon must take into consideration this clinical diagnosis, especially for patients located in an endemic region with occupations that might have exposed the patient to this type of parasite.